2019
DOI: 10.1016/j.ceramint.2018.09.150
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem analysis of alumina-magnesia-carbon refractory bricks used in steelmaking ladles

Abstract: Post-mortem studies in secondary steelmaking ladles are an important way to determine the factors related to Alumina-Magnesia-Carbon (AMC) refractory corrosion. AMC refractory bricks installed in the impact zone of a steelmaking ladle bottom were analyzed after 100 castings. X-ray diffraction, X-ray fluorescence chemical analysis, reflected optical light microscopy, scanning electron microscopy, energy dispersive X-ray spectrometry, density and porosity measurements, and mercury porosimetry were used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…This phenomenon was mainly owing to the great improvement in densification during high-temperature oxidation. 36 , and 4.21 wt% F) was much less pronounced than that for LAC, failing to form a protective layer at the interface. The Al elements showed an obvious graded distribution across the interface as a result of the dissolution of alumina.…”
Section: Industrial Trialmentioning
confidence: 83%
See 1 more Smart Citation
“…This phenomenon was mainly owing to the great improvement in densification during high-temperature oxidation. 36 , and 4.21 wt% F) was much less pronounced than that for LAC, failing to form a protective layer at the interface. The Al elements showed an obvious graded distribution across the interface as a result of the dissolution of alumina.…”
Section: Industrial Trialmentioning
confidence: 83%
“…Undoubtedly, the adhesion of this viscous layer to the interface can inhibit the advance of the liquid slag and thus limit the slag corrosion. 36,37 For the traditional Al 2 O 3 -C refractory, however, the enrichment of Al 2 O 3 in the slag near the interface (containing 25.38 wt% CaO, 14.73 wt% Al 2 O 3 , 40.49 wt% SiO 2 , 1.93 wt% MgO, 8.40 wt% Na 2 O, 2.86 wt% Fe 2 O 3 , and 4.21 wt% F) was much less pronounced than that for LAC, failing to form a protective layer at the interface. This difference was mainly caused by the poor wear resistance of the oxidized layer, which would be easily eroded away by the flux.…”
Section: Industrial Trialmentioning
confidence: 99%
“…When the thermal stress exceeds the limit strength of the ladle nozzle, it will form a crack centered on the casting hole, resulting in thermomechanical erosion. Steel and slag will penetrate through the cracks to the ladle nozzle, and react with the ladle nozzle material, causing thermochemical erosion of the ladle nozzle [2]. In order to improve the service life of the ladle nozzle, it must have good overall performance, such as high temperature resistance, excellent high temperature strength, thermal shock resistance and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The campaign of a steelmaking ladle lined with AMC refractories can last roughly 100 castings, as it was previously reported. 6 In that post-mortem study of AMC bricks, it was concluded that the wear mechanisms on microscopy scale included the formation of a decarburized layer, the thermomechanical spalling when the liquid steel jet was received (at 1973 K), and the subsequent infiltration of slag in the refractory. Finally, the matrix and the oxide aggregates were degraded by erosion or dissolution due to the slag movement.…”
Section: Introductionmentioning
confidence: 99%